2002
DOI: 10.1093/nar/30.8.1817
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative model of human DNA base excision repair. I. mechanistic insights

Abstract: Base excision repair (BER) is a multistep process involving the sequential activity of several proteins that cope with spontaneous and environmentally induced mutagenic and cytotoxic DNA damage. Quantitative kinetic data on single proteins of BER have been used here to develop a mathematical model of the BER pathway. This model was then employed to evaluate mechanistic issues and to determine the sensitivity of pathway throughput to altered enzyme kinetics. Notably, the model predicts considerably less pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 65 publications
4
56
0
Order By: Relevance
“…Similar results have also been obtained with other bifunctional DNA glycosylases such as endonuclease III (hNTH1), responsible for recognition and removal of ring-saturated pyrimidines (36). These studies, in addition to a recent mathematical model of BER throughput (37), suggest a preference for ␤-pol-mediated MFG-BER in vivo.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Similar results have also been obtained with other bifunctional DNA glycosylases such as endonuclease III (hNTH1), responsible for recognition and removal of ring-saturated pyrimidines (36). These studies, in addition to a recent mathematical model of BER throughput (37), suggest a preference for ␤-pol-mediated MFG-BER in vivo.…”
supporting
confidence: 75%
“…Our laboratory has also demonstrated that ␤-pol expression and activity strongly correlate with MFG-BER under a variety of environmental stimuli (52,53,58,59). A recent study (37) examining kinetic data of various BER enzymes has also suggested that ␤-polmediated MFG-BER may be the predominant BER pathway in vivo. As such, the finding that decreased levels of APE in livers of APE-haploinsufficient mice resulted in decreased MFG-BER was surprising.…”
Section: Discussionmentioning
confidence: 73%
“…This implicitly assumes homogeneity and deterministic, continuous reaction kinetics, which are justified by the high concentration of repair proteins as discussed in ref. 28. If Michaelis-Menten assumptions hold for a biochemical system, then k cat is interpreted as the catalytic turnover rate of the enzyme (its ''activity'') and K M is a function of the affinity of the enzyme for the substrate.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Consequently, we apply a mathematical model of human BER that integrates biological knowledge of enzyme mechanisms and biochemical data on enzyme kinetics and protein concentration obtained from the literature. This model has been used to interpret published data from in vitro pathway reconstitution and cell extracts to evaluate mechanistic hypotheses of enzyme cooperativity and coordination and predict the relative significance of the BER subpathways (28). Notably, the model recently predicted that under normal conditions, background oxidative DNA base damage level is at the low end of the widely varying published measurements (i.e., up to hundreds of lesions per cell) and that the background level is relatively stable to small changes in enzyme kinetics (29).…”
Section: Introductionmentioning
confidence: 99%
“…A recent report failed to show 8-oxoGua -containing oligomers in urine (71), implying that further processing occurs, perhaps ultimately yielding 8-oxodG, or that they do not exist. However, under normal circumstances, the role of nucleotide excision repair in the removal of 8-oxoGua and perhaps other small oxidatively generated DNA lesions would seem to be negligible (102)(103)(104)(105)(106), although results from xeroderma pigmentosum cell lines have not entirely excluded the possibility (72,103,107,108). …”
Section: Sources Of Extracellular Oxidatively Modified Dna Lesionsmentioning
confidence: 99%